PENGENALAN POTENSI TEKNOLOGI MBG UNTUK PENGUATAN BUDIDAYA IKAN DI KALIAGUNG KULON PROGO SEBAGAI UPAYA PENANGANAN STUNTING - Astyanto, Achilleus Hermawan; Winarbawa, Heryoga; Roshanti, Fatma; Dyaksa, Gilang Argya; Seen, Michael; Kusbandono, Wibowo; Alapan, Rines; Purwadianto, Doddy (Universitas Sanata Dharma, 2025)
As toddlerhood is a golden milestone during children's growth, high-protein foods like fish are strongly recommended to avoid stunting. On the other hand, a series of proper aeration is often required to support aquaculture in fish farming. Here, the technology of microbubble generators (MBG) can be properly applied. In the present work, subsequent activities which were carried out comprised the design manufacturing, installation, and also trial of MBG units, followed by site exposures. During the first exposure, two sessions covering a talk show and another practical work were conducted. The working principle of MBG was discussed in the first session, while the installation and operation were practically elaborated in the second session. Additionally, in the second exposure, several units of microbubble generators were granted to be applied to the community’s fish farming.